2021
DOI: 10.3390/ijms22158203
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Pills for Drug Addiction: Forced Moderate Endurance Exercise Inhibits Methamphetamine-Induced Hyperactivity through the Striatal Glutamatergic Signaling Pathway in Male Sprague Dawley Rats

Abstract: Physical exercise reduces the extent, duration, and frequency of drug use in drug addicts during the drug initiation phase, as well as during prolonged addiction, withdrawal, and recurrence. However, information about exercise-induced neurobiological changes is limited. This study aimed to investigate the effects of forced moderate endurance exercise training on methamphetamine (METH)-induced behavior and the associated neurobiological changes. Male Sprague Dawley rats were subjected to the administration of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 124 publications
(139 reference statements)
0
9
1
Order By: Relevance
“…Similarly, it has been confirmed in animal studies that the self-administered METH dosage is significantly reduced in mice that voluntarily run on wheels ( 32 - 34 ). Since most drug users lead sedentary lives, studies have reported that rats were subjected to moderate endurance-forced exercise rather than voluntary exercise to mimic the exercise stress conditions found clinically ( 6 , 35 ). In this study, moderate-intensity forced running was used to intervene in the acute withdrawal period of METH-addicted mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it has been confirmed in animal studies that the self-administered METH dosage is significantly reduced in mice that voluntarily run on wheels ( 32 - 34 ). Since most drug users lead sedentary lives, studies have reported that rats were subjected to moderate endurance-forced exercise rather than voluntary exercise to mimic the exercise stress conditions found clinically ( 6 , 35 ). In this study, moderate-intensity forced running was used to intervene in the acute withdrawal period of METH-addicted mice.…”
Section: Discussionmentioning
confidence: 99%
“…The CPP test was conducted every day before the exercise intervention until there was no significant difference between the CPP test and the pretest score for 2 consecutive days, indicating that the CPP had disappeared. The exercise group received treadmill training at a speed of 10 meters/minute, an inclination of 0°, and an acceleration of 8 meters/minute for 45 minutes/day, lasting 7 days in total ( 6 ). All treadmill sessions were scheduled from 9:00 am to 11:30 am.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, exercise may mitigate METH-induced neurotoxicity by preventing BBB destruction in the hippocampus and associated microenvironmental changes [ 96 ]. In SD rats, forced moderate endurance exercise also inhibits METH-induced hyperactivity through the glutamate signaling pathway [ 97 ]. It is not difficult to conclude that the key link between METH-induced neurological damage and the benefits brought by exercise may be the regulation of oxidative stress mechanisms in the above [ 98 ].…”
Section: Exercise Effectively Interferes With Meth Abusementioning
confidence: 99%
“…Both preclinical and clinical studies reported that Nrf2 had a protective effect on METH-induced oxidative stress and inflammation, even neuronal degeneration [ 41 ]. The Nrf2-mediated antioxidant pathway can prevent neurodegenerative effects and functional defects caused by oxidative stress in METH [ 60 , 97 ].…”
Section: Perspective Of Nrf2 In Exercise Prevention and Treatment Of ...mentioning
confidence: 99%